Caught in a 'spiral'. Barriers to healthy eating and dietary health promotion needs from the perspective of unemployed young people and their service providers. (1st February 2015) - Davison, Jenny; Share, Michelle; Hennessy, Marita; Knox, Barbara Stewart
Highlights: Triangulated qualitative design; Food choice in youth not in employment, education or training; Analysis interpreted using Social Cognitive Theory; 'Spiral' of adversity associated with low self-efficacy and control over food choice; Agency (individual and collective) needs enabled by young people themselves. Abstract: The number of young people in Europe who are not in education, employment or training (NEET) is increasing. Given that young people from disadvantaged backgrounds tend to have diets of poor nutritional quality, this exploratory study sought to understand barriers and facilitators to healthy eating and dietary health promotion needs of unemployed young people aged 16–20 years. Three focus group discussions were held with young people (n = 14). Six individual interviews and one paired interview with service providers (n = 7). Data were recorded, transcribed verbatim and thematically content analysed. Themes were then fitted to social cognitive theory (SCT). Despite understanding of the principles of healthy eating, a 'spiral' of interrelated social, economic and associated psychological problems was perceived to render food and health of little value and low priority for the young people. The story related by the young people and corroborated by the service providers was of a lack of personal and vicarious experience with food. The proliferation and proximity of fast food outlets and the high perceived cost of 'healthy' compared to 'junk' food rendered the young people low in self-efficacy and perceived control to make healthier food choices. Agency was instead expressed through consumption of junk food and drugs. Both the young people and service providers agreed that for dietary health promotion efforts to succeed, social problems needed to be addressed and agency encouraged through (individual and collective) active engagement of the young people themselves.